2007
DOI: 10.4028/www.scientific.net/amr.20-21.385
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Substrate and Attachment Substratum on EPS and Biofilm Formation by <i>Acidithiobacillus ferrooxidans</i>

Abstract: Extracellular polymeric substances (EPS) of Acidithiobacillus ferrooxidans and other leaching microorganisms mediate the attachment of cells to pyrite and other minerals. They also play a pivotal role in indirect leaching of base and precious metals via the contact mechanism. The aim of this study is to get more insight on the influence of the growth substrates iron(II) ions, pyrite, chalcopyrite and elemental sulfur on EPS formation, attachment and biofilm formation. The synthesis of EPS by cells of A. ferroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that the nature and quantity of EPS produced and secreted by bioleaching cells is strongly influenced by the culture conditions and the electrochemical characteristics of the substratum (Donlan 2002), and that freeliving (planktonic) cells produce less EPS than cell attached to a mineral (Harneit and Sand 2007); also, that the main EPS produced by bioleaching microorganisms grown on pyrite are neutral polysaccharides (glucose, rhammose, fucose, xylose, and mannose), lipids or saturated fatty acids, and lipopolysaccharides (Gehrke et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the nature and quantity of EPS produced and secreted by bioleaching cells is strongly influenced by the culture conditions and the electrochemical characteristics of the substratum (Donlan 2002), and that freeliving (planktonic) cells produce less EPS than cell attached to a mineral (Harneit and Sand 2007); also, that the main EPS produced by bioleaching microorganisms grown on pyrite are neutral polysaccharides (glucose, rhammose, fucose, xylose, and mannose), lipids or saturated fatty acids, and lipopolysaccharides (Gehrke et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, in medium 1 # , the logarithmic phase of the bacteria started at 12 h and ended at 48 h with a peak cell density of 8.0 × 10 7 cells/mL. There was a slight decrease in bacteria density in the 2 # , 3 # , and 4 # media during the initial growth period, which was attributed to the adsorption of a free population on the surface of elemental sulphur [47,48]. The lag phase of bacteria in the medium with added elemental sulphur was longer than that in the medium using ferrous iron as the sole energy source because of a period of adaptation in the ferrous grown culture to a mixed substrate and sulphur-only environment.…”
Section: Growth Characteristicsmentioning
confidence: 93%
“…A lthough the influence of different properties of the substratum on the formation and evolution of biofilms has been extensively studied by many investigators, [1][2][3][4][5][6][7][8][9] the effect of the deformability of a deformable substratum has not received wide attention except in the recent study by Martin et al, [10] who showed that the geometry of the membrane in Membrane Biofilm Reactors (MBfR) significantly affects the growth rate of the biofilm and hence can be used to enhance the efficiency of the membrane. Bol and Albero [11] developed a model for biological systems growing in an inhomogeneous manner thereby generating residual stresses even when growth rates and material properties are homogeneous.…”
Section: Introductionmentioning
confidence: 99%